Kolaborasi Pemerintah Dengan Stakeholders Dalam Program Kota Tanpa Kumuh Di Kelurahan Belawan Sicanang Kota Medan - Angel Angel; Muhammad Arifin Nasution (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
Due to the limited budget due to complex residential problems, the Medan city government took the initiative to collaborate. Problems in slum areas consist of environmental roads, uninhabitable houses (RLTH) for waste management and ROB flooding. The purpose of this study is to describe the process of collaboration between the government and stakeholders in the KOTAKU program. This study uses a descriptive research method with a qualitative approach. Data collection techniques were carried out by means of observation, interviews and documentation. The research was analyzed through the components as factors in the success of collaboration, namely face-to-face dialogue, building trust, the process of achieving commitment, understanding of joint decisions, obtaining interim results. The results showed that the collaboration process in the City without Slums (KOTAKU) program in Belawan Sicanang Village, Medan City had not been realized properly.